Comparison of Microwave and Ultrasonic Assisted Extraction of Kaempferol from Cassia Alata - Ling Yeong, Yi; Fun Pang, Sook; Yee Chong, Sin; Gimbun, Jolius (International Journal of Engineering and Technology, 2018)
The effect of auxiliary energy to the kaempferol extraction yield from Cassia alata is presented in this paper. The effect of auxiliary energy ranging from 0.045 to 20 W/ml was studied by performing extraction using ultrasonic assisted extraction (UAE), maceration (ME) and microwave assisted extraction (MAE). A ultra-performance liquid chromatography coupled photodiode array (UPLC-PDA) was used for kaempferol identification and quantification. Matching of residence time and UV spectrum between the authentic standard and plant extract was observed to confirm the presence of kaemferol. It was found that MAE method has the highest extraction yield of kaempferol at 21.55 mg/g DW followed by UAE (18.60 mg/g DW) and ME (12.01 mg/g DW). Besides that, the extraction time of MAE was the shortest which is only 4 minutes. The optimum conditions to obtain a high kaempferol yield was achieved using 100% ethanol to extract C. alata powdered leaves with PSD â‰¤125Âµm and plant solid to solvent ratio of 1:20. The findings in this work may serve as a useful guide to obtain highest extraction yield of kaempferol from C. alata.Â Â